Upaya Dalam Menerapkan Pembelajaran Etnosains di Sekolah Dasar: Studi Literatur - Oktaviana, Popy; Rio Aji Pranoto; Khalimatush Sholihah (STAI AL-AMIN, 2024)
Ethnoscience learning implementing culture-based learning will instill an attitude of love for culture and nation. Students will be helped by ethnoscience as a supporting step in forming students' thinking patterns and abilities. This research uses a qualitative method, a type of literature study. By looking for relevant theories that contain reviews, summaries and the author's thoughts. This research was conducted by searching for articles related to efforts to implement ethnoscience learning in elementary schools. The process of assimilation and adaptation of student learning takes place effectively, resulting in student-centered learning. This shows that ethnoscience learning is able to maximize students' learning potential in increasing their understanding of local culture. Efforts that can be applied in learning can be through the use of local learning resources such as local wisdom, folklore, traditional games and traditional food. Ethnoscience learning also has an influence on students' creative thinking processes in increasing students' knowledge.